Pengaruh Model Pembelajaran Two Stay to Stray (TS-TS) Oleh Guru PAK Terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 3 Lintong Nihuta Kabupaten Humbang Hasundutan Tahun Pembelajaran 2023/2024 - Elisabeth Syalom Hutauruk; Johari Manik; Oktober Tua Aritonang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research is to find out whether there is a positive and significant influence of the Two Stay Two Stray (TSTS) learning model on the learning motivation of class VIII students at SMP Negeri 3 Lintong Nihuta, Humbang Hasundutan district for the 2023/2024 academic year. The method used in this research is a quantitative research method with a pre-experimental design research type in the form of